(untitled) (Journal of Material Science and Technology Research, 2025)
The structure of CNC machines must withstand the machining loads and have adequate rigidity to ensure the dimensional accuracy of the product. Gray cast iron is the material normally used in the bases of these machines because it has a relatively low cost, is easy to manufacture, has high compressive strength, and has a high vibration damping capacity. The objective of this work was to develop a rock particle reinforced polymer matrix composite with mechanical properties suitable for the design of precision CNC machining machine structures. Different resin and rock types were analyzed and 3 limestone particulate reinforced composites with 13%, 16% and 23% by weight of epoxy matrix phase were developed, and determinate their mechanical properties through compression tests ABNT NBR 5739/2018 standard. With the obtained values, tests were performed in a finite element software to evaluate the use of the material in the structure of the aircraft aircraft wing CNC machine. The results showed that the best mechanical properties were observed in the composite samples containing 16% epoxy, which by FEM test showed an increase in structural stiffness and a 25% reduction in the maximum deformation resulting from the application of machining loads.